Calidad de la educación - Silva Merino, Jorge (2014)
In this article, it is training to be close of sense and features that take up ofquality education concept. To such purpose, an analysis is made previousof education phenomenon and its relation with paradigms (scientificrevolution). Education quality evaluation is include in the article.Finally, we present some ideas from ERIC CALCAGNO, a Buenos AiresUniversity Teacher, which we consider appropiates for desinging a qualityof education profile.